Framing Media Online Indonesia terhadap isu Regenarasi Petani di Indonesia - Adli; Rasyid, Erwin; Mahmuda, Luqman Abdulloh; Rosyidi, Moch Imron (Borobudur Communication Review, 2026)
Farmer regeneration is a critical issue for the sustainability of agriculture and food security in Indonesia. This study aims to analyze how Indonesian online media frame the issue and its implications for public perception, using Robert N. Entman’s framing analysis supported by Voyant Tools on news data from Antaranews, DetikNews, and TribunNews in 2025. The findings reveal significant differences in framing: Antaranews presents farmer regeneration as a national strategic project emphasizing government roles, centralized policies, and technological solutions; DetikNews highlights localized approaches through regional success stories and the role of local governments; while TribunNews constructs the issue as a social movement driven by youth, collective awareness, and entrepreneurship. In conclusion, there is no single dominant narrative in online media regarding farmer regeneration, resulting in varied public understanding depending on media consumption. This study underscores the importance of an integrative policy approach that combines structural government intervention, local contextual adaptation, and youth empowerment to address farmer regeneration comprehensively.